Impact of Social Isolation on the Behavioral, Functional Profiles, and Hippocampal Atrophy Asymmetry in Dementia in Times of Coronavirus Pandemic (COVID-19): A Translational Neuroscience Approach - Muntsant, Aida; Giménez-Llort, Lydia (Frontiers in Psychiatry, 2020)
The impact of COVID-19 among the old people is devastating and nursing homes are struggling to provide best care to the most fragile. The urgency and severity of the pandemic forces the use segregation in restricted areas and confinement in individual rooms as desperate strategies to avoid the spreading of disease and the worse scenario of becoming a deadly trap. The conceptualization of the post-COVID19 era implies strong efforts to redesign all living conditions, care/rehabilitation interventions and management of loneliness forced by physical distancing measures. Recently, gender differences in COVID-19 found that men have more severe disease and are over twice as likely to die. It’s well known that dementia is associated with increased mortality and males show worse survival and deranged neuro-immuno-endocrine system than females. The present work studies the impact of long-term isolation in male 3xTg-AD mice modeling advanced-stages of Alzheimer’s disease and as compared to age-matched counterparts with normal aging. We used a battery of ethological and unconditioned tests resembling several areas in nursery homes. The main findings refer to an exacerbated (2-fold increase) hyperactivity and emergence of bizarre behaviors in isolated 3xTg-AD mice, worrisome results since agitation is a challenge in the clinical management of dementia and an important cause of caregiver’s burden. This increase was consistently shown in gross (activity in most of the tests) and fine (thermoregulatory nesting) motor functions. Isolated animals also exhibited re-structured anxiety-like patterns and copying-with-stress strategies. Body and kidneys weight loss was found in AD-phenotype, and increased by isolation. Spleen weight loss was isolation-dependent. Hippocampal tau pathology was not modified but asymmetric atrophy of hippocampus - recently described in human patients with dementia- and modeled here for the first time in an animal model of AD, was found increased by isolation. Overall, the results aware about the impact of isolation in the elderly patients with dementia, offering some guidance from translational neuroscience to these times of coronavirus and post-COVID-19 pandemic. They also highlight the relevance of personalized-based interventions tailored to the heterogeneous and complex clinical profile of the individuals with dementia, and to consider the implications on their caregivers’ burden.